2018
DOI: 10.13050/foodengprog.2018.22.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Influential Factors on Supercooling of Nineteen Fruits and Vegetables

Abstract: The main purposes of this study were to identify the factors affecting the supercooling property and to improve the possibility of supercooling storage of fruits and vegetables. Freezing point and nucleation temperature, moisture content, hardness, sugar content, and pH of nineteen fruits and vegetables were measured and Pearson correlation analysis was performed. Freezing point showed a statistically significant correlation with moisture content and sugar content (p<0.01), while ice nucleation temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In fact, Kim et al. (2018) suggested that the key factor affecting supercooled storage of fruits and vegetables is the number of aerobic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Kim et al. (2018) suggested that the key factor affecting supercooled storage of fruits and vegetables is the number of aerobic bacteria.…”
Section: Introductionmentioning
confidence: 99%